2006
DOI: 10.1007/s10340-006-0122-0
|View full text |Cite
|
Sign up to set email alerts
|

Neem oil as a potential seed dresser for managing Homopterous sucking pests of Okra (Abelmoschus esculentus (L.) Moench)

Abstract: Insecticidal seed treatment is an alternative method to spray and granular applications. It can protect the crop right from germination to reproductive stage. Recurrent use of chemical insecticides destabilizes the ecosystem and enhances the development of resistance in pest population. Use of biopesticides like neem oil (NO) is a promising one in this situation. Two field experiments were conducted to test the efficacy of NO as a seed dresser (20 ml kg À1 ) and the effect was compared with systemic chemical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 30 publications
3
2
0
Order By: Relevance
“…The study findings are in line with the results reported by previous workers (Rehman et al, 2015). The application of botanical extracts and chemical insecticides can influence insect pest population and total fruit weight (Ali et al, 2005;Indira Gandhi et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…The study findings are in line with the results reported by previous workers (Rehman et al, 2015). The application of botanical extracts and chemical insecticides can influence insect pest population and total fruit weight (Ali et al, 2005;Indira Gandhi et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…The results are in line with gunasekaran and tangomen [11], who reported that various chemicals especially NSWE for control of okra fruit borer significantly increases the yield of okra.…”
Section: Discussionsupporting
confidence: 89%
“…Application of neemastra and commercial formulation of neem Azadirachtin 3000 PPM @ 5 ml/l have recorded moderate level of leaf miner infestation on French bean in the present study. Similar findings were also reported by Adilakshmi et al (2008); (Ahmed et al, 2007) and Gandhi et al (2006).…”
Section: Effect Of Different Management Practices On French Bean Leaf...supporting
confidence: 89%